Religious Moderation in Indonesian Muslims - Subchi, Imam (Religions, 2022)
Indonesia receives a high religious harmony index every year; however, intolerance and religious radicalism threaten this harmony. Moderate Islam (Islamic religious moderation) has become a national policy as a solution to prevent intolerance and radicalism. In this study, we aimed to determine the factors influencing religious moderation. We examined the variables of religiosity and demographics, which play essential roles in forming religious moderation. A total of 578 students at state Islamic universities in Indonesia participated in this research. We measured religiosity with the Centrality of Religiosity Scale (CRS-5) by Huber and Huber. The CRS-5 consists of five dimensions: intellect, ideology, public practice, private practice, and religious experience, which we adapted to the Indonesian language. The Religious Moderation Scale consists of three dimensions: national commitment, rejecting violence, and accommodating culture. We collected data through questionnaires that we distributed online, and we analyzed the responses using multiple regression analysis. The results show that religiosity positively affected religious moderation, meaning that religious intellectuality, ideology, public practice, private practice, and religious experience supported a person in being moderately religious and might prevent intolerance and radicalism. Socioeconomic factors (sex and parents’ income) also strongly affected religious moderation.